In vitro Evaluation of the Colistin-Carbapenem Combination in Clinical Isolates of A. baumannii Using the Checkerboard, Etest, and Time-Kill Curve Techniques - Soudeiha, Micheline A. H.; Dahdouh, Elias A.; Azar, Eid; Sarkis, Dolla K.; Daoud, Ziad (Frontiers in Cellular and Infection Microbiology, 2017)
The worldwide increase in the emergence of carbapenem resistant Acinetobacter baumannii calls for the investigation into alternative approaches for treatment. This study aims to evaluate colistin-carbapenem combinations against Acinetobacter spp., in order to potentially reduce the need for high concentrations of antibiotics in therapy. This study was conducted on 100 non-duplicate Acinetobacter isolates that were collected from different patients admitted at Saint George Hospital-University Medical Center in Beirut. The isolates were identified using API 20NE strips, which contain the necessary agents to cover a panel of biochemical tests, and confirmed by PCR amplification of blaOXA-51-like. Activities of colistin, meropenem and imipenem against Acinetobacter isolates were determined by ETEST and microdilution methods, and interpreted according to the guidelines of the Clinical and Laboratory Standards Institute. In addition, PCR amplifications of the most common beta lactamases contributing to carbapenem resistance were performed. Tri locus PCR–typing was also performed to determine the international clonality of the isolates. Checkerboard, ETEST and time kill curves were then performed to determine the effect of the colistin-carbapenem combinations. The synergistic potential of the combination was then determined by calculating the Fractional Inhibitory Concentration Index (FICI), which is an index that indicates additivity, synergism, or antagonism between the antimicrobial agents. In this study, 84% of the isolates were resistant to meropenem, 78% to imipenem, and only one strain was resistant to colistin. 79% of the isolates harbored blaOXA-23-like and pertained to the International Clone II. An additive effect for the colistin-carbapenem combination was observed using all three methods. The combination of colistin-meropenem showed better effects as compared to colistin-imipenem (p<0.05). The colistin-meropenem and colistin-imipenem combinations also showed a decrease of 2.6 and 2.8 fold, respectively in the MIC of colistin (p<0.001). Time kill assays additionally showed synergistic effects for a few isolates, and no bacterial re-growth was detected following a 24 hour incubation. Our study showed that the combination of colistin with carbapenems could be a promising antimicrobial strategy in treating CRAB infections and potentially lowering colistin toxicity related to higher doses used in colistin monotherapy.